Analysis of the Effect of Marketing Communication Mix on Consumers’ Buying Interest of OE Bold - Suharko, Adrian; Melinda, Tina (KnE Social Sciences, 2021)
This research aimed to test the influence of Marketing Communication Mix on consumers’ purchase intention of OE Bold, a cigarette product made by PT Ongkowidjojo in Malang. The variables examined were Advertising (X1), Personal Selling (X2), Sales Promotion (X3), and Mobile Marketing (X4). The analytical tool used in this study was multiple linear regression analysis. The population used in this study was the consumer of OE Bold, who made the purchase in each area of the target market of PT Ongkowidjojo (in Sampang, Pamekasan, Sumenep, and Malang) within a month. The questionnaire sample size was 188 respondents. The results were that Advertising (X1), Personal Selling (X2), and Mobile Marketing (X4) variables had a significant influence on the OE Bold consumers’ purchase intention. On the other hand, the Sales Promotion (X3) variable did not have a significant influence on the OE Bold consumers’ purchase intention. Based on the results, the company must retain the aspects that have been assessed well by the consumers and improve the aspects that are considered less good. In subsequent studies we expect to add other variables that have been used in previous studies. Keywords: Advertising, Personal Selling, Sales Promotion, Mobile Marketing